2019
DOI: 10.15421/021938
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cell-free extracts of Bifidobacterium bifidum and Lactobacillus reuteri on proliferation and biofilm formation by Escherichia coli and Pseudomonas aeruginosa

Abstract: The development of new effective preparations for the correction of microecological disorders based on probiotic derivatives requires a comprehensive study of the biological activity of the latter. We studied the proliferative activity and biofilm formation by clinical isolates: Escherichia coli and Pseudomonas aeruginosa under the influence of cell-free extracts containing structural components and metabolites of the Bifidobacterium bifidum and Lactobacillus reuteri probiotic strains. Cell-free extracts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
1
3
1
3
Order By: Relevance
“…The results obtained versus P. aeruginosa do not differ much from the results obtained by Aminnezhad et al, who demonstrated the antimicrobial activity of CFS produced by L. casei and L. rhamnosus against P. aeruginosa (MIC of 62.5 µL/mL) whose antimicrobial activity has been hypothesized to be associated with the presence of lactic acid, acetic acid, and hydrogen peroxide [58]. Moreover, Alakomi et al, (2000) demonstrated that lactic acid, in addition to exerting its antimicrobial effect due to a pH decrease, also acts as a membrane-permeabilizing of Gram-negative bacterial outer membrane thus favoring the entry of other antimicrobial agents [59].…”
Section: Discussioncontrasting
confidence: 53%
“…The results obtained versus P. aeruginosa do not differ much from the results obtained by Aminnezhad et al, who demonstrated the antimicrobial activity of CFS produced by L. casei and L. rhamnosus against P. aeruginosa (MIC of 62.5 µL/mL) whose antimicrobial activity has been hypothesized to be associated with the presence of lactic acid, acetic acid, and hydrogen peroxide [58]. Moreover, Alakomi et al, (2000) demonstrated that lactic acid, in addition to exerting its antimicrobial effect due to a pH decrease, also acts as a membrane-permeabilizing of Gram-negative bacterial outer membrane thus favoring the entry of other antimicrobial agents [59].…”
Section: Discussioncontrasting
confidence: 53%
“…Effect of cell-free extracts on proliferative activity of clinical isolates was studied using spectrophotometric microplate method previously described in detail [23]. Briefly, an increase in the optical density of test cultures was compared in the presence (test samples) or absence (control samples) of the studied cell-free extracts.…”
Section: Methodsmentioning
confidence: 99%
“…Безклітинні екстракти (БКЕ) отримували з пробіотичних штамів В. bifidum 1 («Біфідумбактерин», ТОВ «Віво-Актив», Україна) та L. reuteri DSM 17938 («БіоГая», BioGaia Production AB, Швеція). Методика отримання БКЕ докладно описана раніше [7]. Досліджено чотири види БКЕ: L − екстракт з дезінтеграту бактерій L. reuteri; ML − екстракт з культури L. reuteri, що культивувалася у дезінтеграті власних клітин; B − екстракт з дезінтеграту бактерій В. bifidum; MB − екстракт з культури B. bifidum, що культивувалася у дезінтеграті власних клітин.…”
Section: матеріали та методи дослідженняunclassified